2021
DOI: 10.1021/jacs.0c11357
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting and Metallic [5,5] Fullertube Nanowires: Characterization of Pristine D5h(1)-C90 and D5d(1)-C100

Abstract: Although fullerenes were discovered nearly 35 years ago, scientists still struggle to isolate "single molecule" tubular fullerenes larger than C 90 . In similar fashion, there is a paucity of reports for pristine single-walled carbon nanotubes (SWNTs). In spite of Herculean efforts, the isolation and properties of pristine members of these carbonaceous classes remain largely unfulfilled. For example, the low abundance of spherical and tubular higher fullerenes in electric-arc extracts (<0.01−0.5%) and multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 36 publications
4
61
0
Order By: Relevance
“…A 1g (10) at 1195 cm −1 is another medium-intensity Raman feature of C 100 largely originating from ungerade CNT vibration, this time B 2u (2) predicted at 1319 cm −1 . This CNT mode, mixed with B 1g (1) ( predicted at 1377 cm −1 ), also contributes to the second strongest non-resonant Raman feature of C 100 , A 1g (12) at 1301 cm −1 . In fact, the latter can be described as the Kekule vibration of the belt hexagons.…”
Section: Normal Mode Analysis For C 100 -D 5dmentioning
confidence: 86%
See 1 more Smart Citation
“…A 1g (10) at 1195 cm −1 is another medium-intensity Raman feature of C 100 largely originating from ungerade CNT vibration, this time B 2u (2) predicted at 1319 cm −1 . This CNT mode, mixed with B 1g (1) ( predicted at 1377 cm −1 ), also contributes to the second strongest non-resonant Raman feature of C 100 , A 1g (12) at 1301 cm −1 . In fact, the latter can be described as the Kekule vibration of the belt hexagons.…”
Section: Normal Mode Analysis For C 100 -D 5dmentioning
confidence: 86%
“…Fortuitously, the studies of tubular fullerenes, aka fullertubes, gained the new boost with the discovery of the isolation route based on their reduced chemical reactivity. 10,12 While fullerenes usually readily react with amino-alcohols, tubular fullerenes appeared to be significantly less reactive, which allowed their facile separation from other fullerenes. The main fullertubes obtained this way are C 90 -D 5h , C 96 -D 3d , and C 100 -D 5d (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Stevenson and Xie et al. successfully isolated several typical isomers of pristine fullertubes like D 5h (1)‐C 90 , D 3d (3)‐C 96 and D 5d (1)‐C 100 by selective chemical enrichment [6a,b] . Notably, the changes from semiconductors to metallic state have also been demonstrated, and such results indicate the unique electronic properties of fullertubes [6b] .…”
Section: Introductionmentioning
confidence: 99%
“…successfully isolated several typical isomers of pristine fullertubes like D 5h (1)‐C 90 , D 3d (3)‐C 96 and D 5d (1)‐C 100 by selective chemical enrichment [6a,b] . Notably, the changes from semiconductors to metallic state have also been demonstrated, and such results indicate the unique electronic properties of fullertubes [6b] . Chlorination is an effective strategy for capturing different isomers of fullertubes, but skeleton transformation usually occurs [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Of broad interest is whether fullertubes behave as fullerenes (C 60 , C 70 ), as single wall nanotubes (SWNTs), or neither. In 2021, a study showed a transition to metallic properties by inserting 10 carbon atoms from the shorter [5,5] C 90 -D 5h (1) fullertube to the longer [5,5] C 100 -D 5d (1) fullertube. In 2022, an excited state study of [5,5] C 90 -D 5h (1) fullertubes showed photophysical properties consistent with classical fullerenes.…”
mentioning
confidence: 99%